The Effect of Dietary Changes in Controlling the Hypertension in Sleman Yogyakarta - Kusumo, Mahendro Prasetyo; Anggraini, Panji Tutut (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2019)
Background: Hypertension is the disease with the highest number of cases among patients who visit primary care. Most hypertension is caused by a poor diet. One of the main causes of hypertension is poor food control. This study aimed to know the effect of diet control education intervention against the behavior changes in controlling the blood pressure for hypertensive patients. Methods: This study used the quasi-experimental design with pre-test and post-test with a control group. The intervention and control groups were chosen through the implemented criteria of inclusion and exclusion. The used sampling technique was a simple random sampling. There were 84 subjects of hypertensive patients. The subjects were divided into two groups, i.e., 42 patients (intervention group) and 42 patients (control group). The intervention was done for six weeks. Result: There were differences in dietary control behavior changes between the control and intervention groups. The intervention group had significant (p<0,05) change,1.41 while control group had decreased in score (∆) (0.47) where the value of p was not significant, (p>0.05). The average value of systolic blood pressure for the intervention group was 4.47 mmHg/5.17 mmHg, and the increase of the average value of systolic blood pressure was 3.63 mmHg/5.95 mmHg for the control group. Conclusion: Dietary control education influences blood pressure control for hypertensive patients.